Propuesta de mejora del nivel de calidad en una organización de educación superior técnica en Arequipa aplicando la metodología DMAIC - Arista Valdivia, Adriana Sofía (2021)
The research sought to improve the level of quality in the teaching-learning process in a technical higher education institution in the city of Arequipa through continuous improvement, using the Define, Measure, Analyze, Control and Improve (DMAIC) methodology.We identified the main requirements on the part of the students, such as: the application of active teaching methodologies to facilitate the learning of the courses, the use of Information Technology tools (ICTs) during the development of the classes, availability of specialist teachers and correctly implemented laboratories to guarantee the practical application of knowledge. In addition, we determined the Six sigma level (6σ) and the current Process Capacity (Cp) value of each specialty to verify if the institution is capable of meeting the requirements of the students, obtaining as an average result a sigma level of 3 and a Cp of 1. This means that the technical training service provided fails tofully cover the student's requirements. From the analysis, it was possible to identify the main causes that affect the quality of the institution's service. Among them we can mention the reduction of quality standards to carry out the evaluation of transversal courses, the lack of monitoring and control of the teacher training plan, finally, the lack of knowledge of the structure of active methodologies by the teacher.Consequently, the research details different improvement proposals to mitigate and eliminate the main failures mentioned. These include the design of a program to reinforce transversal courses and study techniques, the establishment of a training procedure for teachers, and particularly the design of a training program on active methodologiesand ICT tools for teachers.With the implementation of these improvement proposals, the number of students disapproved in transversal courses will be reduced by 5% per year, the teacher's productivity will be improved from 60 to 84% and it will decrease until 9% the percentage of disapproved students in specialty courses.The economic evaluation carried out based on the implementation of the detailed proposals will require an investment of S/. 116'938.41, and recognizing the effectiveness of the application of the proposals, it is projected to obtain a positive Incremental Net Present Value (NPV) of S/. 814,067 and an Incremental Cost Benefit of 10.00 over a period of 03 years, meaning that the benefits of the project exceed the investment and operating costs, therefore, the project is profitable.